Characterization of Sucrose-Negative Pasteurella multocida Variants, Including Isolates from Large-Cat Bite Wounds - Christensen, Henrik (American Society for Microbiology, 2005)
To validate the identification of Pasteurella multocida-like bacteria negative for acid formation from sucrose, including isolates from bite wounds caused by large cats, 17 strains were phenotypically and genotypically characterized. Phylogenetic analysis of partially sequenced rpoB and infB genes showed the monophyly of the strains characterized and the reference strains of P. multocida. The sucrose-negative strains formed two groups, one related to reference strains of P. multocida and the other related to a separate species-like group (taxon 45 of Bisgaard). DNA-DNA hybridization further documented the species-like nature of this group. Ribotyping showed the heterogeneity of all strains except four strains that shared the same ribotype and that were isolated from bovine lungs. Phylogenetic analysis by 16S rRNA sequence comparison showed the monophyly of the strains characterized and the reference strains of P. multocida. Two strains isolated from leopard bite wounds were related to the type strain of P. dagmatis; however, they represented a new taxon (taxon 46 of Bisgaard), in accordance with their distinct phenotypic and genotypic identifications. The present study documents that sucrose-negative strains of P. multocida-like bacteria belong to two genotypically distinct groups. The study further confirms the phenotypic heterogeneity of P. multocida strains and documents two new species-like taxa of Pasteurella related to P. multocida. Until diagnostic tools have been further elaborated, special care should be taken in the identification of Pasteurella-like bacteria isolated from bite wounds caused by large cats. The evidence of phenotypic and genotypic divergence calls for the further development of PCR tests and DNA sequencing to document doubtful isolates.